2022
DOI: 10.1155/2022/6413553
|View full text |Cite
|
Sign up to set email alerts
|

Progress on Brain and Ocular Lymphatic System

Abstract: In recent years, 2 major discoveries have modified the traditional understanding of the brain. First, meningeal lymphatic vessels (MLV) were found in the dural sinus, which may absorb and drain cerebrospinal fluid (CSF). Second, the glymphatic system was discovered, composed of para-arterial CSF influx channel, paravenous interstitial fluid (ISF) efflux channel, and the water channel aquaporin-4 (AQP4) in astrocytes connecting the 2 channels. Accumulating evidence demonstrates that the lymphatic system of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 57 publications
0
7
0
Order By: Relevance
“…Although the brain parenchyma is devoid of lymphatic vessels, the rapid clearance of cellular debris and metabolic products in the central nervous system is attributable to the glymphatic system and meningeal lymphatic vessels. 103 The glymphatic system is composed of three essential components: the para-arterial cerebrospinal fluid influx channel, the para-venous interstitial fluid efflux channel, and the water channel aquaporin-4 in astrocytes that connect these channels. 103 Cerebrospinal fluid flows into the brain through the para-arterial space and exchanges with interstitial fluid via aquaporin-4; this type of exchange drives metabolite and interstitial fluid into the para-venous space and then into the cerebrospinal fluid circulatory system or directly through the capillary lymphatics into the cervical lymphatics.…”
Section: Biological Functions Of Lymphatic Vessels and Related Regula...mentioning
confidence: 99%
See 1 more Smart Citation
“…Although the brain parenchyma is devoid of lymphatic vessels, the rapid clearance of cellular debris and metabolic products in the central nervous system is attributable to the glymphatic system and meningeal lymphatic vessels. 103 The glymphatic system is composed of three essential components: the para-arterial cerebrospinal fluid influx channel, the para-venous interstitial fluid efflux channel, and the water channel aquaporin-4 in astrocytes that connect these channels. 103 Cerebrospinal fluid flows into the brain through the para-arterial space and exchanges with interstitial fluid via aquaporin-4; this type of exchange drives metabolite and interstitial fluid into the para-venous space and then into the cerebrospinal fluid circulatory system or directly through the capillary lymphatics into the cervical lymphatics.…”
Section: Biological Functions Of Lymphatic Vessels and Related Regula...mentioning
confidence: 99%
“… 103 The glymphatic system is composed of three essential components: the para-arterial cerebrospinal fluid influx channel, the para-venous interstitial fluid efflux channel, and the water channel aquaporin-4 in astrocytes that connect these channels. 103 Cerebrospinal fluid flows into the brain through the para-arterial space and exchanges with interstitial fluid via aquaporin-4; this type of exchange drives metabolite and interstitial fluid into the para-venous space and then into the cerebrospinal fluid circulatory system or directly through the capillary lymphatics into the cervical lymphatics. In particular, the glymphatic system transports lipids within the brain.…”
Section: Biological Functions Of Lymphatic Vessels and Related Regula...mentioning
confidence: 99%
“…It is still unclear whether they have a lymphatic system and how they eliminate metabolites from the optic nerve and retina. Recent studies have found that the ocular lymphatic system has a crucial impact on ocular diseases, such as optic nerve and retinal disorders [4].…”
Section: The Glymphatic Systemmentioning
confidence: 99%
“…Nevertheless, recent reports have confirmed the presence of meningeal lymphatic vessels (MLV) in the dura mater [ 2 , 5 ] and the existence of prelymphatic channels connected to the perivascular space able to drain effectively the interstitial fluid and assure the cleaning of the cerebral interstitial environment, the so-called glymphatic system [ 6 ]. Finally, even the retina [ 7 , 8 , 9 ], optic nerve [ 9 , 10 , 11 ], and conjunctive region [ 9 , 12 , 13 ] present MVL or glymphatic systems.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, the exchange and removal of metabolites have shown great value and significance in the study of central nervous system diseases such as Alzheimer’s and subarachnoid hemorrhage, highlighting the importance of the lymphatic system in the central nervous system as well [ 9 ].…”
Section: Introductionmentioning
confidence: 99%